Comparison of Fractional CO₂ Laser versus Combined Platelet Rich Plasma and Fractional CO₂ Laser in Treatment of Post-Acne Scars - Shifa Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post-acne scarring is a common sequela of acne vulgaris and often causes psychosocial burden. Fractional CO₂ laser resurfacing and platelet-rich plasma (PRP) are widely used treatments. Several studies suggest that combining PRP with fractional CO₂ laser may improve outcomes, but evidence comparing the two approaches directly remains limited. Methods: This randomized prospective clinical study was conducted at Department of Dermatology Khyber Teaching Hospital Peshawar from Jan 2022 to June 2022 with included 110 patients aged 18 to 40 years with moderate to severe atrophic acne scars. Patients were assigned to Group A (fractional CO₂ laser alone) or Group B (combined PRP plus fractional CO₂ laser). All patients received three monthly sessions. Outcomes were assessed using the Global Acne Scar Score (GASS), the Visual Analog Scale (VAS) for satisfaction, and standardized photographs. Cox regression analysis was used to estimate the likelihood of significant scar improvement. Results: Both groups showed significant improvement, but Group B achieved greater reductions in GASS and higher VAS scores. Demographic characteristics were similar between groups. Cox regression indicated that the combined treatment increased the likelihood of achieving significant improvement, with a hazard ratio of 2.3 (p = 0.01). Conclusion: PRP combined with fractional CO₂ laser is more effective than fractional CO₂ laser alone for improving atrophic post-acne scars. The combination enhances collagen remodeling and yields better clinical and patient-reported outcomes. Keywords: Acne scars, Fractional CO₂ laser, Platelet-rich plasma, PRP, Laser resurfacing, Scar remodeling, Aesthetic dermatology